Inflation Targeting and Quantitative Tightening: Effects of Reserve Requirements in Peru - Adrián Armas; Paul Castillo; Marco Vega (Inter-American Development Bank (IDB), 2014)
This paper provides an overview of the reserve requirement measures undertaken by the Central Bank of Peru. It provides a rationale for the use of these instruments as well as empirical evidence of their effectiveness. In general, the results show that tightening reserve requirements has the desired effects on interest rates and credit levels at both banks and smaller financial institutions (cajas municipales).
hdl:11319/6445
Keywords: E51; E52; E58; G21; 330; Nonconventional monetary policy; Inflation targeting; Reserve requirements